Electronic and magnetic properties of ABO3 perovskites (A - Ca, Ce, Y, Na; B - Ti, Nb, Fe, Mn, Ta; O) - P. A. Praskurava; D. S. Hvazdousky; M. S. Baranava; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article presents the results of quantum-mechanical computer simulation. The purpose of studying the electronic and magnetic properties of twenty crystalline structures based on perovskites of transition metals with the general formula ABO3 (where A - Ca, Ce, Y, Na; B - Ti, Ta, Nb, Mn, Fe ion; O - oxygen ion) is to assess the possibility of using this group of materials in modern electronic devices. Systematization of fundamental characteristics will allow further describing of the physical mechanisms that occur in structures. Calculations of the fundamental properties of crystals were performed using first-principle methods based on the density functional theory (Density Functional Theory - DFT). The VASP software package (Vienna Ab initio Simulation Package) was used as the simulation tool, which is designed to perform quantum-mechanical calculations. As a result of the simulation, the following characteristics of perovskites of transition metals were established: ABO3 unit cells have cubic syngony; a number of compounds have a magnetic moment (from 0.26 to 4.39 p®); an analysis of the band structures shows the presence of compounds with a semiconductor (band gap from 1.65 to 2.99 eV) and metallic type of conductivity. The direct-gap type of conductivity was established for only CeTiO3 compound. The results obtained quantitatively and qualitatively characterize the electronic and magnetic properties of crystalline structures based on ABO3 perovskites and can be used to develop methods for calculating the basic electrophysical parameters of promising electronic components.